Plant derived substances with anti-cancer activity: from folklore to practice - Fridlender, Marcelo; Kapulnik, Yoram; Koltai, Hinanit (Frontiers in Plant Science, 2015)
Plants have had an essential role in the folklore of ancient cultures. In addition to the use as food and spices, plants have also been utilized as medicines for over 5000 years. It is estimated that 70-95% of the population in developing countries continues to use traditional medicines even today. A new trend, that involved the isolation of plant active compounds begun during the early 19th century. This trend led to the discovery of different active compounds that are derived from plants. In the last decades, more and more new materials derived from plants have been authorized and subscribed as medicines, including those with anti-cancer activity. Cancer is among the leading causes of morbidity and mortality worldwide. The number of new cases is expected to rise by about 70% over the next 2 decades. Thus, there is a real need for new efficient anti-cancer drugs with reduced side effects, and plants are a promising source for such entities. Here we focus on some plant-derived substances exhibiting anti-cancer and chemoprevention activity, their mode of action and bioavailability. These include paclitaxel, curcumin and cannabinoids. In addition, development and use of their synthetic analogs, and those of strigolactones, are discussed. Also discussed are commercial considerations and future prospects for development of plant derived substances with anti-cancer activity.